A Novel Medial Canthal Reconstruction Technique in Children With Blepharophimosis Syndrome. Issue 5 (September 2019) - Parvizi, Sahar; Ong, Juling; Abou Rayyah, Yassir; Dunaway, David
Abstract : Purpose: There are different techniques for medial canthoplasty in blepharophimosis syndrome where individuals have epicanthus inversus and telecanthus leading to typical facial appearances. These methods have potential problems with scarring, epistaxis, and extrusion of metal plates. Methods: The authors describe a novel technique of medial canthal reconstruction using titanium microplates with microscrew fixation to the anterior lacrimal crest, with effective, safe, and reproducible results. Results: Seven children with blepharophimosis syndrome underwent medial canthus reconstruction surgery at a single center with the collaboration of a pediatric oculoplastic surgeon and craniofacial plastic surgeon to improve eye opening through correction of the lid contours and telecanthus. Conclusions: This is a safe, effective, and reproducible technique, with minimal morbidity and rapid postoperative recovery in children. It produces cosmetically acceptable scars and a strong stable reconstruction of the medial canthal insertion. Abstract : The authors describe a safe and stable medial canthoplasty reconstruction method in children with blepharophimosis.